Estudo da fração lectínica da apitoxina da abelha Apis mellifera L. (Hymenoptera: Apidae) - TAVARES, Caio Pavão (2016)
Animal venoms have great importance for biotechnology, due to its wealth of components and biological applications. The apitoxin, bee venom of Apis mellifera L., is used as a pharmacological tool for the treatment of diseases as arthritis, cancer and fight against HIV. Lectins have been identified as components of various venoms. Lectin is a class of proteins, non-immunological origin, able to bind specific, reversible and non-covalently to carbohydrates or glycoconjugates. In the present work, we demonstrate the isolation and partial biochemical characterization of lectinic fraction from bee venom of Apis mellifera L. The bee venom was derived from bees raised in apiaries in São Bento, Maranhão, with electric collector use. The isolation of lectin fraction was accomplished by bioaffinity chromatography (affinity matrices of galactomannans). The fractions were analyzed by native and SDS-PAGE electrophoresis. The same fractions were subjected to the hemagglutination test on blood types A, B, AB and O followed by haemagglutination inhibition test for carbohydrates (glucose, mannose, galactose, sucrose and lactose). The divalent cations requirement test was performed using EDTA in hemagglutination system. The fraction was subjected to heating stability test where the samples were exposed to temperatures of 40, 50, 60, 70, 80, 90 and 100° C for 30 minutes and subsequently subjected to the determination of hemagglutinating activity. One lectin fraction D-galactose-biding and recognize α-galactosides was isolated from bee venom. It is 3,2% of the dry weight of bee venom. The electrophoresis analysis under denaturing conditions indicated that this fraction showed three bands with molecular weights of approximately 14, 17 and 19 kDa. When subjected to electrophoresis native (no SDS), the lectin fraction revealed only one band at the top of the gel, suggesting that these bands are subunits of the same protein. The hemagglutination activity was observed for the four human blood types, however, it showed greater sensitivity to the red cells of type A (2048 U.H./mL). The hemagglutination activity of this fraction was inhibited by lactose (150mM) and D-galactose (500mM), thus providing specificity for these two carbohydrates. EDTA (MIC = 0,156 mM) was also capable of inhibiting the hemagglutination activity, indicating that this lectin fraction is dependent on divalent cations. The isolated lectin fraction showed high thermostability being able to maintain its activity even after exposure to 70° C for 30 minutes. The bee venom of africanized bee Apis melliferra L. has no previous reports of the presence of lectins.